Complex dynamics of climate emotions among environmentally active Finnish and American young people - Coppola, Isabel; Pihkala, Panu (Frontiers in Political Science, 2023)
Climate emotions have become an increasingly salient issue in recent years. This paper draws on data from in-depth interviews from the United States (USA) and Finland to provide insight into the complex dynamics of climate emotions in 23 environmentally active young people in these two countries. The analysis centers on three main themes: complex dynamics of climate emotions, identities and felt social expectations, and coping mechanisms. Through this analysis, this article contributes to the understanding about the ways in which identities and felt social expectations shape climate emotions including feelings of inadequacy and obligation. It also explores coping mechanisms used by these young activists and points to the need to include positive emotional approach coping in research frameworks. Analysis of the experiences of this limited number of young people shows the prevalence of feelings of inadequacy and thus supports the recent arguments about the need to provide young people tools to set their responsibility in context, in order to avoid negative consequences of the felt pressures. The results also support recent research about the importance of anger, grief and guilt as very common climate emotions among active people, even though a broad range of emotions was recognized by the participants.